The threat of Cyberterrorism and the applicability of the convention of cybercrime - Zulhuda, Sonny (Islamic Military Counter Terrorism Coalition (IMCTC), 2020)
The proliferation of information and communications technology, merged with the increasing amount of big data and interconnectivity, turns out to be a deadly combination when it comes to the threat of terrorism. Just like any industry that grows up with the new technologies, criminals and terrorists would certainly make use of the sophistication of the Internet, mobile gadgets and artificial intelligence in order to launch their terrorist agenda. This is indeed the new challenges faced by the global community.